Valid and accurate simple equation to predict 3,000-m steeplechase performance - Barbry, Alexis; Lerebourg, Lucie; Racil, Ghazi; Jlid, Mohamed Chedly; Coquart, Jérémy (Frontiers in Sports and Active Living, 2024)
Introduction Predict running performances is very important for athletes and trainers. Sport researchers have therefore developed certain tools to predict running performances, but only in non-obstacle races. This study aimed to develop and test the validity and accuracy of an equation for predicting 3,000-m steeplechase performance (PerfSteeple). Methods The official rankings of French runners for the 3,000-m track-running (Perf3000) and 3,000-m steeplechase events were examined. Age, height and body mass were collected. From 146 included athletes, two groups were randomly composed: one comprising 80% of the sample (n = 117) to develop a simple equation to predict PerfSteeple (i.e., development group) and the other comprising the remaining 20% (n = 29) to test the validity and accuracy of the developed prediction equation (i.e., cross-validation group). Results The simple prediction equation included Perf3000 and age: PerfSteeple=−57,165+1,147×Perf3000+0,955×age. No significant difference was noted between the actual and predicted performances. Predicted performances were significantly correlated with the actual ones, with a very high correlation coefficient (p < 0.001; r = 0.929). Bias and 95% limits of agreement were −5 ± 24 s, i.e., −0.8 ± 7.6%. In 95 of 100 new predictions, the difference between actual and predicted performance would be less or equal to—5 ± 24 s. Discussion The study confirms the validity and accuracy of the equation for predicting PerfSteeple. Predictions using this simple equation may be used in training and competitions for athletes and coaches. PerfSteeple = −57,165 + 1,147 X Perf3000 + 0,955 X age.